2020
DOI: 10.1016/j.jviromet.2020.113920
|View full text |Cite
|
Sign up to set email alerts
|

Development of a SYBR Green quantitative PCR assay for detection of Lates calcarifer herpesvirus (LCHV) in farmed barramundi

Abstract: Lates calcarifer herpes virus (LCHV) is a new virus of farmed barramundi in Southeast Asia.2 However, a rapid detection method is yet to be available for LCHV. This study, therefore, 2 aimed to develop a rapid quantitative PCR (qPCR) detection method for LCHV and made it 2 timely available to public for disease diagnostics and surveillance in barramundi farming 3 countries. A newly designed primer set targeting a 93-bp fragment of the LCHV putative 3 major envelope protein encoding gene (MEP) was used for deve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…In Singapore, where this particular study has taken place, farmers have reported mass mortalities of juveniles during the transition between nursery phases (∼50 to 500 g) and the final grow out period as a recurring phenomenon over the last few years. Although several novel viral pathogens (SDDV, LCHV, LCBV) affecting barramundi have been first reported and identified in Singaporean farms (Gibson-Kueh et al, 2012;de Groof et al, 2015;Chang et al, 2018;Chen et al, 2019), their occurrence is now known to extend throughout Southeast Asia (Senapin et al, 2019;Nurliyana et al, 2020;Meemetta et al, 2020), affecting the industry as a whole. To better understand what is happening to the biology of barramundi in commercial farming conditions during one such disease outbreak, the presence of five putative pathogens was investigated using a comparative RNAseq and histological approach targeting multiple organs of affected and non-affected juveniles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Singapore, where this particular study has taken place, farmers have reported mass mortalities of juveniles during the transition between nursery phases (∼50 to 500 g) and the final grow out period as a recurring phenomenon over the last few years. Although several novel viral pathogens (SDDV, LCHV, LCBV) affecting barramundi have been first reported and identified in Singaporean farms (Gibson-Kueh et al, 2012;de Groof et al, 2015;Chang et al, 2018;Chen et al, 2019), their occurrence is now known to extend throughout Southeast Asia (Senapin et al, 2019;Nurliyana et al, 2020;Meemetta et al, 2020), affecting the industry as a whole. To better understand what is happening to the biology of barramundi in commercial farming conditions during one such disease outbreak, the presence of five putative pathogens was investigated using a comparative RNAseq and histological approach targeting multiple organs of affected and non-affected juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…Copy numbers of SDDV and LCHV were calculated from respective standard graphs generated by qPCR amplifications of serially diluted plasmid containing corresponding viral insert target as previously described (Meemetta et al, 2020;Sriisan et al, 2020).…”
Section: Screening Of Five Putative Fish Pathogens By Pcr Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Serial dilutions of the pSNB1 plasmid spiked with 200 ng of tilapia DNA were used to construct a standard curve for quantifying S. agalactiae . Fish gill DNA was isolated using the conventional phenol-chloroform method [31,32] and 200 ng of each DNA sample was subjected to qPCR assays using the CFX Connect™ Real-time System (Bio-Rad, USA). The resulting C q value was used to compute bacterial DNA in the fish gills using the equation: copy number = 10 (Ct – Intercept)/Slope .…”
Section: Methodsmentioning
confidence: 99%